THE CLASSIC MOZART MUSIC THERAPY ON BASAL METABOLIC RATE (BMR) IN PREMATURE INFANTS AT PERINATOLOGY OF BANYUMAS HOSPITAL - Desiyani Nani; Oktriani Utami; Acik Yuli Purwanti (Jurnal Ilmiah Kesehatan Keperawatan, 2013)
Prematurity associated with lower body weight and basal metabolic rate (BMR). One form of treatment of premature infants is music therapy as a form of stimulation in nursing children. This research aims to determine the differences within each treatment group the classic Mozart music therapy for basal metabolic rate (BMR). This research used quasi-experiment approach to pre and post test design without control group. Samples using consecutive sampling with a total of 14 respondents. The collection of data used observation sheet. Processing the data used a statistical test Friedman and repeated Anova. The results showed the value of p value 0.007 in the classic Mozart music therapy duration of 15 minutes (A), and the p value 0.818 in the classic Mozart music therapy duration of 30 minutes (B). The result U-Mann Whitney test got p>α=0,05. There is a significant influence on the group A, and there is no significant effect on the BMR group B. And there is no difference between groups A and B. The result U-mann Whitney test before therapy got p= value 0,848, after 3 days therapy got p value 0,277, and after 6 days therapy got p value 0,224. Need to increase the number of samples, conducting research at the same time, and conducted research with the number of men and women the same to be divided between the two treatment groups. Keywords: Classic Mozart Music Therapy premature infants,, body weight, basal metabolic rate (BMR)